Electrochemical Synthesis of Ammonia in Solid Electrolyte Cells - Garagounis, Ioannis; Kyriakou, Vasileios; Skodra, Aglaia; Vasileiou, Eirini; Stoukides, Michael (Frontiers in Energy Research, 2014)
Developed in the early 1900s, the “Haber–Bosch” synthesis is the dominant NH3 synthesis process. Parallel to catalyst optimization, current research efforts are also focused on the investigation of new methods for ammonia synthesis, including the electrochemical synthesis with the use of solid electrolyte cells. Since the first report on Solid State Ammonia Synthesis (SSAS), more than 30 solid electrolyte materials were tested and at least 15 catalysts were used as working electrodes. Thus far, the highest rate of ammonia formation reported is 1.13 × 10-8 mol s-1 cm-2, obtained at 80°C with a Nafion solid electrolyte and a mixed oxide, SmFe0.7Cu0.1Ni0.2O3, cathode. At high temperatures (>500°C), the maximum rate was 9.5 × 10−9 mol s-1 cm-2 using Ce0.8Y0.2O2-δ–[Ca3(PO4)2–K3PO4] as electrolyte and Ag–Pd as cathode. In this paper, the advantages and the disadvantages of SSAS vs. the conventional process and the requirements that must be met in order to promote the electrochemical process into an industrial level are discussed.